Project Management for Building Construction 35 Years of Innovation at Drees & Sommer - Sommer, Hans (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Without professional project management, successful execution of major projects is no longer conceivable today. Very practice-oriented, and building on more than 35 years of innovation in the field of project management, this book outlines profiles of the most important market participants, the essential contents of the planning and construction process as well as the tasks of the project manager, his or her methods and tools. Particularly, the obligation of the project manager is pointed out when it comes to carrying out the process of project execution in a transparent and effective manner in order to guarantee, together with the other project participants involved, the maximum degree of usefulness, design, sustainability and profitability at specified costs and deadlines. The book addresses project managers, project developers and construction experts but also to the responsible representatives of the clients and investors who have recognized that sustainable and economical design are going to be the topics of the future in the building and property industries.